Survey of Student's Interest in the Traditional Game of Handang In SMP Negeri 4 Buton, Buton Regency - Rifky Nekirari; Jacob Anaktototy; Siti Divinubun (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research will describe how much students' interest in the traditional hadang game at SMPN 4 Buton, Buton Regency. Based on the calculation results, it can be explained that students' interest in the traditional game hadang 20% ​​(10 respondents) obtained a low score, 32% (16 respondents) obtained a moderate score, 44% (22 respondents) obtained a high score and 4% (2 respondents) obtained a very high score. Based on the data obtained in the study, it can be concluded that students' interest in traditional hadang games 20% (10 respondents) obtained a low score, 32% (16 respondents) obtained a moderate score, 44% (22 respondents) obtained a high score and 4% (2 respondents) got a very high score. Starting from the results of the analysis, it can be concluded that students' interest in the traditional hadang game is in the high category with a percentage of 44%.